ASUHAN KEBIDANAN IBU HAMIL, BERSALIN, NIFAS, BBL, NEONATUS DAN KB FISIOLOGIS PADA NY S USIA 35 TAHUN DI UPTD PUSKESMAS KERTEK 1 KABUPATEN WONOSOBO - Ika Zuliyanti, Nurma; Sulistyani, Menik (Jurnal Komunikasi Kesehatan, 2025)
COC covers various stages, starting from pre-pregnancy health education, care during pregnancy, childbirth, topost-natal care and family planning programs. To provide continuous health care for mothers and babies, startingfrom pre-pregnancy education to family planning programs. Comprehensive midwifery care has been carried out inaccordance with independent midwifery care and early handling. No complications were found from pregnancy,childbirth, postpartum, BBL, and KB.